L‐serine: a neglected amino acid with a potential therapeutic role in diabetes. Issue 10 (2nd September 2019) - Holm, Laurits J.; Buschard, Karsten
Abstract : L‐serine is classified as a non‐essential amino acid; however, L‐serine is indispensable having a central role in a broad range of cellular processes. Growing evidence suggests a role for L‐serine in the development of diabetes mellitus and its related complications, with L‐serine being positively correlated to insulin secretion and sensitivity. L‐serine metabolism is altered in type 1, type 2, and gestational diabetes, and L‐serine supplementations improve glucose homeostasis and mitochondrial function, and reduce neuronal death. Additionally, L‐serine lowers the incidence of autoimmune diabetes in NOD mice. Dietary supplementations of L‐serine are generally regarded as safe (GRAS) by the FDA. Therefore, we believe that L‐serine should be considered as an emerging therapeutic option in diabetes, although work remains in order to fully understand the role of L‐serine in diabetes.